PERAN PEMIMPIN, ORGANISASI PEMBELAJAR DAN KOMPETENSI ORGANISASI, SERTA DAMPAKNYA PADA KINERJA ORGANISASI - NURWANTI NURWANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
The purpose of this study is to determine and analyze role of the leaders, learning organization, and competence of the performance studies program. Other than that, to determine the effect of role of the leaders by learning organization and competence, also it’s impact on the performance of the study program. The research carried out on an accredited S1 courses in Private collages in Jakarta, the method used in this research is survey method, which are descriptive survey and explanatory survey. Structural Equation Model was used as the analysis technique along with PLS, number of sample in total of 110 courses. Determination of the sample using Stratified Random Sampling, which is the three strata of accreditation ratings: A, B, and C, the proportional of the total of 611 courses. The result of the research show that there is a influence over role of the leaders, the variable learning organization and competence on performance, that the better role of the leaders, learning organization and increasing competence will impact performance. The impact of the competence against the performance is small, which means the competence of the course not always give a dominant influence for the performance